Developing mHealth Apps with researchers: multi-stakeholder design considerations - Craven, Michael P.; Lang, Alexandra. R.; Martin, Jennifer L. (Springer, 2014)
The authors have been involved with developing a number of mHealth smartphone Apps for use in health or wellness research in collaboration with researchers, clinicians and patient groups for clinical areas including Sickle Cell Disease, Attention Deficit Hyperactivity Disorder, asthma and infertility treatment. In these types of applications, end-users self-report their symptoms and quality of life or conduct psychometric tests. Physiological data may also be captured using sensors that are internal or external to the device. Following a discussion of the multiple stakeholders that are typically involved in small scale research projects involving end-user data collection, four Apps are used as case studies to explore the issue of non-functional requirements.